Numerical modeling of nonlinear Newwaves for impact assessment on offshore structures - Burger, W.J. (author) (2005)
Offshore structures are designed to resist the impact of the extreme wave. Shell EP Projects desires a computer model that is able to simulate the impact of the design wave on gravity based offshore platforms, such as the Sakhalin PA-B platform. Comflow is a numerical model that simulates fluid flow, by solving the Navier-Stokes equations using the improved Volume-of-Fluid method. The wave inflow is prescribed at a side boundary of the Comflow domain. Shell uses the Newwave theory to prescribe the wave group that contains the design wave. The shape of the wave train that contains the design wave is important for the impact on the structure as it influences wave run up and reflection; possibly causing the wave to slam against the bottom of an offshore platform deck. Shallow water and wave steepness influence the shape of the wave group; this can be simulated with nonlinear wave models. This thesis concerns the simulation of nonlinear Newwaves and the implementation in Comflow. The goals of the thesis hence are to: 1. Find a wave model to simulate fully nonlinear Newwaves. 2. Couple the nonlinear wave model to Comflow. 3. Validate the wave impact on structures in Comflow with scale model tests. Vijfvinkel [25] developed a quasi-spectral method to solve the wave potential equation; the one dimensional spatial domain is periodic and it requires solely an initial condition. The method is based on expansion of the Dirichlet-Neumann operator, which is substituted in the governing equations. The operator consists of the surface elevation and the velocity potential at the surface. These are the properties that are calculated in a time domain. A velocity profile can be reconstructed. The Vijfvinkel computer code was obtained and revitalised. The Beji Battjes test [3] was simulated in Comflow. It confirmed the grid and time step requirements [19], and it showed that the nonlinear formation and release of higher harmonics are also simulated correctly following the requirements. Three additional numerical tests were set up ...